German technology policy strikes new paths: A few remarks on the region-oriented innovation policy of the Federal Government - Dohse, Dirk (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
Since the mid 1990’s the German Federal Ministry of Education and Research strikes a new path in technology funding by tying technology policy initiatives to the regional level. The BioRegio contest and the InnoRegio contest are considered to be the prototype models of this new policy. The current paper analyses and compares the two prototype models and elaborates conceptual strengths and weaknesses of region oriented technology policy.